1996
DOI: 10.1159/000164032
|View full text |Cite
|
Sign up to set email alerts
|

HIV and the 7-Transmembrane Domain Receptors

Abstract: The recent discovery of a chemokine receptor, fusin (fusin/CXCR-4), as the long-sought human immunodeficiency virus type 1 (HIV-1) coreceptor opened an entirely new field of aquired immunodeficiency syndrome (AIDS) research on mechanisms of viral entry, tropism and pathogenesis. It was soon followed by the identification of the chemokine receptor CCR-5 as the major macrophage-tropic (M-tropic) HIV-1 coreceptor and the demonstration that other chemokine receptors, CCR-3 and CCR-2b, also may serve as coreceptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Together, these findings suggested that in certain cells with low CD4 densities, the relative levels of CCR5 and CXCR4 expression and their ability to associate with CD4 may influence the susceptibility of the cells to infection with X4 and R5 viruses, as was previously speculated (5). In the present study, we provide evidence that CCR5 and CXCR4, when expressed in the same cell, interfere with each other's function during HIV-1 envelope-mediated cell fusion and viral cell entry.…”
Section: Conversely Overexpression Of Cxcr4 Compared With Ccr5 Inhibsupporting
confidence: 67%
“…Together, these findings suggested that in certain cells with low CD4 densities, the relative levels of CCR5 and CXCR4 expression and their ability to associate with CD4 may influence the susceptibility of the cells to infection with X4 and R5 viruses, as was previously speculated (5). In the present study, we provide evidence that CCR5 and CXCR4, when expressed in the same cell, interfere with each other's function during HIV-1 envelope-mediated cell fusion and viral cell entry.…”
Section: Conversely Overexpression Of Cxcr4 Compared With Ccr5 Inhibsupporting
confidence: 67%
“…Although some 15 related coreceptor molecules have been shown by one or more laboratories to function in the fusion or entry of at least one HIV isolate, it is now well recognized that the principal HIV-1 coreceptors remain the initially discovered CXC chemokine receptor CXCR4 and the CC-chemokine receptor CCR5 (7,21). Previously, it was hypothesized that the very first step in HIV-1 entry involves the formation of a trimolecular complex between the viral Env, CD4, and a coreceptor molecule (18,33,52), and both functional and biochemical evidence to support this hypothesis has been reported (35,59,84,88,90). Defining the elements of the coreceptor molecules involved in these interactions is of critical importance for our understanding of the virus entry mechanism.…”
mentioning
confidence: 99%
“…This is either directly, through antibody-dependent cell-mediated cytotoxicity (2,18,38,43), or indirectly, through the production of chemokines; CC-chemokine ligand 3 (CCL3; also called MIP-1␣), CCL4 (MIP1-␤), and CCL5 (RANTES), which are natural ligands of CCR5 (10) and which block viruses that utilize the CCR5 coreceptor for entry (5,6,9,13,16,26). NK cells also produce cytokines, including gamma interferon (IFN-␥), granulocyte/ macrophage colony-stimulating factor, and tumor necrosis factor alpha which can suppress HIV replication by recruiting other effector cells (16).…”
Section: Cd16mentioning
confidence: 99%